Co-overexpression of AVP1 and PP2A-C5 in Arabidopsis makes plants tolerant to multiple abiotic stresses. (September 2018) - Sun, Li; Pehlivan, Necla; Esmaeili, Nardana; Jiang, Weijia; Yang, Xiaojie; Jarrett, Philip; Mishra, Neelam; Zhu, Xunlu; Cai, Yifan; Herath, Maheshika; Shen, Guoxin; Zhang, Hong
Highlights: Simultaneously over-expressing AVP1 and PP2A-C5 as linked genes. Further increase tolerance to NaCl at high concentrations. Combining beneficial traits from overexpressing AVP1 and PP2A-C5 . Multiple gene overexpressing help plants deal with multiple stresses. Abstract: Abiotic stresses are major threats to agricultural production. Drought and salinity as two of the major abiotic stresses cause billions of losses in agricultural productivity worldwide each year. Thus, it is imperative to make crops more tolerant. Overexpression of AVP1 or PP2A-C5 was previously shown to increase drought and salt stress tolerance, respectively, in transgenic plants. In this study, the hypothesis that co-overexpression of AVP1 and PP2A-C5 would combine their respective benefits and further improve salt tolerance was tested. The two genes were inserted into the same T-DNA region of the binary vector and then introduced into the Arabidopsis genome through Agrobacterium-mediated transformation. Transgenic Arabidopsis plants expressing both AVP1 and PP2A-C5 at relatively high levels were identified and analyzed. These plants displayed enhanced tolerance to NaCl compared to either AVP1 or PP2A-C5 overexpressing plants. They also showed tolerance to other stresses such as KNO3 and LiCl at harmful concentrations, drought, and phosphorus deficiency at comparable levels with either AVP1 or PP2A-C5 overexpressing plants. This study demonstrates that introducing multiple genes in single T-DNA region is an effective approach to create transgenic plants with enhanced tolerance to multiple stresses.